THE EFFECTIVENESS OF HIGH INTENSITY INTERVAL TRAINING WITH BLOOD FLOW RESTRICTION TRAINING ON ANAEROBIC THRESHOLD IN RUNNERS - Adyasputri, A A I Ayesa Febrinia; Kamayoga, I Dewa Gede Alit; Dewi, Ni Luh Ayu Srianti (Sport and Fitness Journal, 2021)
The performance of runners is related to the anaerobic threshold level. Anaerobic threshold plays an important role in runner’s endurance. Anaerobic threshold value is also closely related to the level of runner’s fatigue when doing physical exercise or when competing for a long time. If the body’s endurance level cannot withstand the activities carried out, it will give a negative effect on their performance. There are exercises that aim to increase the anaerobic threshold value, namely high intensity interval training and blood flow restriction training. High intensity interval training can increase the anaerobic value through the mechanism of provide a high stimulus to anaerobic glycolytic and carbonic anhydrase reaction with formation (H + ) that improved buffering capacity. Addition of blood flood restriction training by using limb occlusion pressure causes local hypoxia, so it will increase muscle metabolic demand. It will induce metabolic acidosis with increased hydrogen ions and lactate production. Key Words: High Intesity Interval Training; Blood Flow Restriction; Anaerobic Threshold; Anaerobic Capacity; Runners